Answers

2016-08-06T08:09:07+08:00
[secx + tanx].[secx + tanx]= [1 + sinx]/1-sinx

secx=1/cosx; tanx = sinx/cosx;

[1/cosx + sinx/cosx].[1/cosx + sinx/cosx] =[1+sinx]/[1-sinx];

[cosx +sinxcosx]/cos^2x .[cosx +sinxcosx]/cos^2x;
factor;

[cosx[ 1 +sinx]/cos^2x]. [cos[1 +sinx]/cos^2x;

cancel x;

[1+sinx]/cosx. [1+sinx]/cosx=[1+sinx]/1-sinx;

[1+sinx].[1+sinx]/cos^2x=[1+sinx]/[1-sinx];

hence: cos^2x= 1-sin^2x

[1+sinx][1+sinx]/1-sin^2x= [1+sinx]/1-sinx];

[1+sinx][1+sinx]/[1-sinx][1+sinx];

cancell : [1+sinx];

[1+sinx]/1-sinx]=[1+sinx]/1-sinx]


0